The 7th French Airborne Forward Surgical Team experience of surgical support to the population of a low-income country: a prospective study on 341 patients with short-term follow-up. Issue 6 (9th June 2018) - Goudard, Yvain; Butin, C; Carfantan, C; Pauleau, G; Soucanye de Landevoisin, E; Goin, G; Clement, D; Bordes, J; Balandraud, P
Abstract : Background: The 7th Airborne Forward Surgical Team (FST) has deployed to Chad in 2015 and 2016, in support of French military forces. Humanitarian surgical care is known to represent a significant part of the surgical activity in such missions, but to date limited data have been published on the subject. Methods: All surgical patients from a civilian host population treated by the FST during these missions have been prospectively included. Indications, operative outcomes and postoperative outcomes were evaluated. Results: During this period, the FST operated on 358 patients. Humanitarian surgical care represented 95% of the activity. Most patients (92.7%) were operated for elective surgery. Emergencies and infectious diseases represented, respectively, 7.3% and 9.1% of cases. The mean length of stay (LOS) was three days (2–4), and the median follow-up was 30 days (22–34). Mortality rate was 0.6% and morbidity was 5.6%. Parietal surgery had no significant complication and had shorter LOS (p<0.001). Emergent surgeries were more complicated (p<0.01) and required more reoperations (p<0.05). Surgical infectious cases had longer LOS (p<0.01). Conclusions: Humanitarian surgical care can be provided without compromising the primary mission of the medical forces. Close surveillance and follow-up allowed favourable outcomes with low morbidity and mortality rates. Humanitarian care is responsible for a considerable portion of the workload in such deployed surgical teams. Accounting for humanitarian care is essential in the planning and training for such future medical operations.